Dampak Penerapan Penerapan SIKAP Terhadap Aspek Produktivitas Kerja pada Bagian Perencanaan dan Keuangan Sekretariat Daerah Kabupaten Agam - Pratiwi Suryaningsih; Afridian Wirahadi Ahmad (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2023)
This study aims to determine the impact of applying the SIKAP application in the aspect of work productivity in the Planning and Finance Section of the Regional Secretariat of Agam Regency. To make it easier to recap daily work reports, the Agam Regency Government has implemented a Government Apparatus Performance Information System (SIKAP) since 2018 where previously the daily performance reporting of ASN Employees was done manually. The use of the SIKAP application is outlined in the Amendment to the Regent's Regulation concerning Additional Employee Income (TPP). To see the Work Productivity of ASN employees, they are required to make a Work Daily report (LKH), which is a record of the implementation of ASN Employee duties every working day in accordance with their authority and responsibilities. Which will have an impact on TPP acceptance. The SIKAP application was created to fulfill the Corruption Eradication Commission's (KPK) Regional Action Plan (RAD) which requires the use of an application to facilitate fast and ready-to-use data processing, more guaranteed validity, ease of data entry for daily performance reports. And to facilitate control from the leadership so that it is more efficient in reducing paper use and speeding up data processing. The method used is the Census method for ASN Employees. The results of the study stated that the impact of implementing the SIKAP application on aspects of work productivity has supported the implementation of work and needs to be implemented properly and maximally to obtain TPP.